Lumion 3D cookbook : revolutionize your Lumion skills with over 100 recipes to create stunning architectural visualizations - Cardoso, Ciro (Quick answers to common problems., 2014)
This book offers uses practical applications using recipes with step-by-step instructions and useful information to help you master how to produce professional architectural visualizations in Lumion. The cookbook approach means you need to think and explore how a particular feature can be applied in your project and perform the intended task. This book is written to be accessible to all Lumion users and is a useful guide to follow when becoming familiar with this cutting-edge real-time technology. This practical guide is designed for all levels of Lumion users who know how to model buildings i.